Pharmacological Properties of Metal (Silver, Copper, and Iron) Nanoparticles - Chekman, I.S. (Science and Innovation, 2024)
The paper contains summarized results of studies on the pharmacological and specific properties of nanometals (silver, iron, and copper). The acute toxicity of metal nanoparticles depends on their nature, way of administration, and sex of laboratory animals. The nanoparticle effect on the heart activity, the hemodynamic status, and the osmotic resistance of erythrocyte membranes depend on the dose administered.